Molecular Detection of Bovine Meat Adulteration in Bangladesh Using Multiplex-PCR of the Mitochondrial Cytochrome B Gene (Bioresearch Communications, 2026)
Meat and meat product fraud poses a serious threat to food safety and public health, as it may lead to metabolic disorders, allergic reactions, and infections. Beyond health concerns, such adulteration also violates market, ethical, and religious principles. To address this issue, multiplex PCR techniques targeting the mitochondrial cytochrome b gene were optimized to evaluate the authenticity of various meat and meat products in Bangladesh. Raw meat samples of bovine (Bos indicus), pig (Sus scrofa domesticus), and canine (Canis lupus familiaris) were collected, with some portions cooked, to establish and optimize multiplex-PCR protocols.The optimized multiplex-PCR method successfully detected pig and canine meat adulteration in bovine meat, even at varying proportions. Both raw and cooked samples demonstrated high sensitivity, being able to detect adulterants as low as 10%. To validate the PCR results, sequencing and analysis of the amplified products confirmed species-specific identification. Additionally, fried bovine meat samples (n = 5) collected from Bangladeshi restaurants were tested and found to be free of adulteration.This study highlights the effectiveness of multiplex-PCR as a reliable tool for detecting meat adulteration in both raw and cooked products. The method showed high sensitivity and accuracy, making it suitable for routine monitoring of meat authenticity. While continuous surveillance and strict regulatory enforcement remain essential, the optimized PCR-based techniques can play a vital role in strengthening food safety and ensuring consumer trust in Bangladesh.Bioresearch Commu. 12(2): 2115-2122, 2026 (January)